Associations between essential metals exposure and metabolic syndrome (MetS): Exploring the mediating role of systemic inflammation in a general Chinese population. (July 2020) - Ma, Jixuan; Zhou, Yun; Wang, Dongming; Guo, Yanjun; Wang, Bin; Xu, Yiju; Chen, Weihong
Graphical abstract: Highlights: Urinary copper and zinc were positively associated with MetS prevalence. Urinary copper and zinc were positively associated with plasma CRP. Higher concentration of plasma CRP was positively related to MetS prevalence. Associations of copper and zinc with MetS was partly mediated through CRP. Abstract: Background: Essential metals have been reported to be associated with metabolic diseases. However, the relationships between essential metals exposure and Metabolic Syndrome (MetS) is still uncertain, and the underlying mechanisms of the association remain unclear. Objectives: To investigate the associations of urinary essential metals with MetS prevalence; and further to explore potential role of systemic inflammation biomarker, C-reactive protein (CRP), in relationships between essential metals exposure and MetS prevalence in a cross-sectional study. Methods: Concentrations of 8 urinary essential metals and plasma C-reactive protein (CRP) were quantified in 3272 adults from Wuhan-Zhuhai cohort. Urinary essential metals were adjusted by the corresponding urinary creatinine concentrations and reported as μg/mmol creatinine. Multivariable logistic regression and linear regression models were used to evaluate dose–response relationships between essential metals, plasma CRP, and MetS prevalence. Mediation analysis was performed to investigate the role of plasma CRP in the associations between urinary essential metals and MetS prevalence. Results: In the single-metal models, we observed positive dose-dependent relationships of urinary copper and zinc with MetS prevalence. Compared with the lowest quartiles of urinary metals, the ORs (95% CI) of MetS in the highest quartiles were 1.40 (1.03, 1.91) for urinary copper and 2.07 (1.51, 2.84) for zinc, respectively. The dose-dependent relationships of zinc and copper with MetS remained significant in the multiple-metal models and Bayesian kernel machine regression (BKMR) models. No significant associations were observed between others essential metals (e.g. manganese, iron, cobalt, selenium, chromium, molybdenum) and MetS in this general population (all P value > 0.05). In addition, urinary copper and zinc increased monotonically with plasma CRP elevation, and plasma CRP was positively associated with the MetS prevalence. Mediation analysis indicated that plasma CRP mediated 5.2% and 3.2% in the associations of urinary copper and zinc with MetS prevalence, respectively. Conclusions: Elevated concentrations of urinary copper and zinc were associated with increased prevalence of MetS. Systemic inflammation may play an important role in the associations of copper and zinc exposure with MetS.